Pembelajaran Fikih dengan Media Video - Sufni Sufriah; Al Ikhlas (Prodi Pendidikan Keagamaan Islam, 2023)
The background to this research problem is the different understanding between theory and practice in learning Jurisprudence in Class VII MTsN 1 Kota Padang. Therefore innovation is needed in learning, one of which is the use of video media in the learning process so that learning is more varied and enjoyable. This study aims to determine Jurisprudence Learning with Video Media in Class VII MTsN 1 Padang City. This type of research is descriptive research and the method used is qualitative research methods. The results of the research are about Jurisprudence Learning with Video Media in Class VII MTsN 1 Padang City which is going well, Jurisprudence learning with video media is very appropriate because it triggers student enthusiasm and enthusiasm. Learning that teaches about variations in learning and fun learning. Lastly, Jurisprudence learning with video media is synonymous with practical learning or practice that is carried out in everyday life, making it easier for students to understand all Jurisprudence material.